Reproductive cycle of a non-native oyster, Crassostrea gigas, in the Adriatic Sea - EZGETA BALIĆ, DARIA; RADONIĆ, IVANA; BOJANIĆ VAREZIĆ, DUBRAVKA; ZORICA, BARBARA; ARAPOV, JASNA; STAGLIČIĆ, NIKA; JOZIĆ, SLAVEN; PEHARDA, MELITA; BRISKI, ELIZABETA; LIN, YAPING; ŠEGVIĆ-BUBIĆ, TANJA (Mediterranean Marine Science, 2020)
The Pacific oyster Crassostrea gigas was introduced for the aquaculture purposes in many different parts of the world. However, the species has never been officially introduced for commercial farming in the Croatian part of the Adriatic Sea. Interestingly, in the 1970s, the Pacific oyster has been reported in the natural habitats of the Lim Bay, in northern Adriatic Sea. Although the species was recorded there, there is a lack of knowledge about its biology and ecology in this region, including a reproductive cycle. Information on the reproductive biology of non-indigenous species in new areas is crucial for prediction of their future survival and possible spread in invaded habitats. In this study, we provide the first data on the reproductive biology of the Pacific oyster in the Adriatic Sea, the northernmost part of the Mediterranean Sea. Quantitative and qualitative methods of gonad tissue analysis were conducted, and effects of environmental conditions on the gametogenesis were evaluated during two reproductive cycles. Our study confirmed that environmental conditions in the Lim Bay were favourable for the reproduction of the species. The Pacific oyster reproduced once per year and had a prolonged spawning period. Water temperature was the main factor affecting gonad development and oocyte size, while chlorophyll a concentration had an impact on the oocyte development in terms of their size.